Religion in Hellenistic Athens - Mikalson, Jon D. (Hellenistic culture and society, 1998)
Religion in Hellenistic Athens, like Greek religion in the classical period and Christianity at later times, was a complex system of deities, rituals, and beliefs that responded to human needs. As the needs and circumstances of the Athenians changed, so changed their religion, but very gradually. I emphasize the word change, a neutral term, because the understanding of Hellenistic religion and of Athenian religion in particular has been significantly impeded by value judgments either condemning them as degenerating from the classical ideal or praising them for making progress toward Christian conceptions. In the most general terms, the devaluation of Hellenistic religion has led to cynicism about the motives